A novel evaporative cooling system with a polymer hollow fibre spindle. (5th March 2018) - Chen, Xiangjie; Su, Yuehong; Aydin, Devrim; Ding, Yate; Zhang, Shihao; Reay, David; Riffat, Saffa
Highlights: A novel micro porous hollow fibre module is utilized as the humidifier in an evaporative cooling system. The fibres were made into a novel spindle shape in order to allow maximum contact between the air and water. The working performance with respect to various incoming air dry bulb temperature were experimentally studied. The hollow fiber module proves to offer superior heat and mass transfer performance. Experimentally derived heat and mass transfer correlations were summarized and compared with results from literature. Abstract: A polymer hollow fibre evaporative cooling system with a novel configuration of fibre bundle is proposed. With the aim to avoid the flow channelling or shielding of adjacent fibres the fibres inside each bundle were made into a spindle shape to maximize contact between the air stream and the fibres. For the porous wall of hollow fibre, the vapour of evaporated water can permeate through it effectively, while the liquid water droplets can be prevented from mixing with the processed air. For various dry bulb temperatures (27 °C, 30 °C, 33 °C, 36 °C and 39 °C) and relative humidity (23%, 32% and 40%) of the inlet air, the cooling performances of the proposed novel evaporative cooling system were experimentally investigated. The variations of outlet air dry bulb temperature, wet bulb effectiveness, dew point effectiveness and cooling capacity with respect to different incoming air dry bulb temperature were studied. The effects of various incoming air Reynolds number on the heat and mass transfer coefficients, heat flux and mass flux across the polymer hollow fibre module were analysed. Experimentally derived non-dimensional heat and mass transfer correlations were compared with other correlations from literature. Due to the proposed spindle shape of hollow fibre bundle, the shielding between adjacent fibres could be mitigated greatly, therefore the heat and mass transfer performance of the proposed system demonstrated significant improvement compared with other designs reported in literature.